Fowler syndrome post liposculpture and augmentation mammoplasty: Case report and literature review - Rodrigo Domínguez-Millán; Tatiana Luna Pisciotti; Pamela Fernández Cuesta; Miguel Angel Bonilla Becerril (JPRAS Open)
Fowler syndrome is a rare entity that occurs in young women, with a high incidence of polycystic ovary syndrome. It consists of episodes of acute urinary retention that have a characteristic electromyographic pattern. Its etiology is unclear and is usually preceded by a trigger such as a surgical procedure, childbirth, other acute medical conditions, and opioid use. There is no report in the literature that links any Plastic Surgery procedure to Fowler Syndrome. We present the case of a 31-year-old female patient who had an episode of acute urinary retention 36 hours after liposculpture and augmentation mammoplasty. Infectious, anatomical and functional causes were ruled out upon admission to the emergency room, confirming the diagnosis of Fowler Syndrome. The patient was treated with bladder catheterization for 72h and tamsulosin for 15 days, with adequate response. Subsequent to this she presented a favorable evolution without new episodes of difficulty for urination, without functional sequelae or complications in the aesthetic surgical result.